2017
DOI: 10.1002/biof.1404
|View full text |Cite
|
Sign up to set email alerts
|

Less fibrosis in elderly subjects supplemented with selenium and coenzyme Q10—A mechanism behind reduced cardiovascular mortality?

Abstract: The significantly decreased biomarker concentrations in those on active treatment with selenium and coenzyme Q10 compared with those on placebo after 36 months of intervention presumably reflect less fibrogenic activity as a result of the intervention. These observations might indicate that reduced fibrosis precedes the reported improvement in cardiac function, thereby explaining some of the positive clinical effects caused by the intervention. © 2017 BioFactors, 44(2):137-147, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…In a previous publication our group presented data indicating less fibrosis in seven out of eight evaluated biomarkers for fibrosis in the population receiving SeQ 10 compared with those on placebo. This could indicate a possible anti-ageing effect on the cardiovascular system, as the ageing process is highly associated with increased fibrosis of the cardiovascular system [59]. Increased expression and synthesis of selenoprotein P following selenium supplementation requires SAM-dependent protein methylation [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous publication our group presented data indicating less fibrosis in seven out of eight evaluated biomarkers for fibrosis in the population receiving SeQ 10 compared with those on placebo. This could indicate a possible anti-ageing effect on the cardiovascular system, as the ageing process is highly associated with increased fibrosis of the cardiovascular system [59]. Increased expression and synthesis of selenoprotein P following selenium supplementation requires SAM-dependent protein methylation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Было также замечено, что через 48 месяцев после начала исследования уровень марке-ра NT-proBNP в группе, принимающей добавки, был значительно ниже, чем в группе плацебо (214 нг / л против 302 нг / л, р=0,014), что указывает на меньшие риски развития сердечной недостаточности. Изучение результатов эхокардиографии сердца выявило значительное улучшение сердечных функций у людей, принимавших комбинацию веществ, при сравнении с результатами, полученными от группы плацебо [56].…”
Section: эффекты селена в составе различных структурunclassified
“…Among trials conducted in patients with CVD, CoQ10 was tested alone or with antioxidant supplements [ 45 , 46 , 47 , 48 , 49 ] and beneficial effects included decreased fibrosis, morbidity, and mortality, as well as decreased levels of pro-inflammatory cytokines, with improved left ventricular function and quality of life. A clinical trial conducted in CVD patients by McMackin et al [ 18 ], testing a combination of ALA and acetyl-CARN, reported a significant improvement of blood pressure and vascular tone.…”
Section: Mitochondrial Nutrient-based Clinical Trials In Aging-relmentioning
confidence: 99%
“…Two other clinical trials [ 50 , 51 ] were conducted on acyl-CARN in CVD patients, which also reported positive effects on CVD endpoints, as well as OS parameters such as decreased concentrations of malondialdehyde and 4-hydroxynonenal. Altogether, one may recognize that CVD patients may benefit from adjuvant treatments with CoQ10, ALA, and acyl-CARN [ 18 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Mitochondrial Nutrient-based Clinical Trials In Aging-relmentioning
confidence: 99%